Artificial immune system optimization technique for optimal location and parameter setting of UPFC: article / Siti Noor Aishah Mohamad Ariffin - Mohamad Ariffin, Siti Noor Aishah (2010)
This project paper is about to find optimal location for parameter setting of Unified Power Flow Controller (UPFC) at line data in transmission line from bus system by using Artificial Immune System (AIS) programming technique. The performance of this technique was tested on IEEE 26-Bus reliability test system. The minimum total losses and total cost are determined and the lowest values is selected as the best optimal location to place UPFC at 3 lines of transmission line.